EMPLOYING MULTIMEDIA-BASED LEARNING TO IMPROVE ENGLISH SPEAKING SKILLS - Ahmad Thoyyib Shofi (Universitas PGRI Yogyakarta, 2020)
Regarding language learning today, everyone is increasingly awarded that traditional language teaching is no longer effective in supporting students need. Learning speaking skills in the classroom carry out by the lecturers are still using traditional methods conducting learning in the classroom using whiteboards, markers, and other manual tools. Meanwhile, in the current global era, multimedia based learning is a demand along with the development of technology. Therefore, this article elaborates the mechanism of multimedia used in learning speaking skills. The type of research was Classroom Action Research (CAR) with the subject were the second semester students of The University of Qomaruddin Gresik. This Classroom Action Research process was taken in two cycles with 4 procedure; planning, implementation, observation, and reflection. The result of the cycle one shown that 10 students or 50% of 20 students spoke English too slow and repeated the same sentence many times so the listener could not understand the meaning, so their speaking skill were in poor level. Meanwhile, 50% or 10 the rest of the students got good level. Since the result of the cycle one was below the target, so the researcher continued to conduct the second cycle. After the second cycles were conducted, the result shown that 25% students was in good level, and 75% students were in very good level. After the second cycle was conducted, finally the level of the students’ speaking skill was increasing, so the researcher ended the research.